Comparison of the Effectiveness of Video Based Learning Methods and Peer Group Methods on Increasing Knowledge of Young Women Consuming Blood Supplement Tablets at SMPN 4 Kota Baru Cikampek Karawang - Eni Margi Lestari; Novita Novita (STIKep PPNI Jawa Barat, 2023)
Aims : Blood supplement tablets are tablets to prevent anemia in adolescents, but in reality there are still many adolescents who do not know about these supplements. One of the efforts made to increase knowledge is to provide health education or education using media such as video based learning and peer group methods. Methods : A pre-experimental demham one-group pretest-posttest design was employed in this investigation. To collect knowledge data before and after the intervention, a one-group pre-post test design was used. In this study, 58 young women who met the inclusion criteria were sampled. A questionnaire was utilized to collect data, and the results were analyzed using a paired test. Results : The average score of knowledge after being given Video Based Learning was 15.91 and after being given the Peer group method was 12.98. The results of the test using the paired T test showed that there was an effect of the Video Based Learning Method and the peer group method on the knowledge of young women in taking iron supplement tablets (each p value 0.000). The Video Based Learning Method and the Peer Group Method are more effective in increasing the knowledge of young women in consuming iron supplement tablets with a p value of 0.000 Conclusions : Video Based learning and the Peer group method can affect youth knowledge, but Video Based learning is more effective in increasing knowledge about TTD. Therefore midwives are advised to provide health education to adolescents using video media.